Prognostic biomarkers in ischemic stroke treated with mechanical thrombectomy: a systematic review - Rodrigues, Rodrigo Fellipe; Hidalgo, Raquel Cristina Trovo; Batista, Savio; Lopes, Júlia Belone; Mantovani, Gabriel Paulo; Oliveira, Pedro Henrique Matos; Nishizima, André; Corin, Anderson Silva; Macedo, Lucas; Maximiano, Mariana Letícia de Bastos; Magalhães, Pedro Lucas Machado; Ricci, Julia Camargo; Oliani, Sonia Maria (Arquivos de Neuro-Psiquiatria, 2025)
Mechanical thrombectomy (MT) is a key therapy for acute ischemic stroke (AIS), improving survival and functional outcomes. However, the variability in results highlights the need for predictive markers to refine patient selection. Biomarkers reflecting inflammation and metabolic stress are gaining recognition for their role in AIS and MT outcomes.To systematically review and synthesize the evidence on biomarkers associated with clinical outcomes in AIS patients undergoing MT. Specific aims include evaluating their relationship with functional recovery (mRS), mortality, infarct volume, hemorrhagic transformation, and complications such as malignant brain edema (MBE) and delayed cerebral ischemia (DCI).A systematic review of the literature was conducted in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement to identify studies evaluating biomarkers in MT. The PubMed and Embase databases were searched using the following terms: (Marker OR biomarker*) AND (Mechanical Thrombectomy OR endovascular) AND Stroke.Of 2,834 articles identified, 86 met inclusion criteria. Several biomarkers, such as C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), adenosine deaminase (ADA), neuron-specific enolase (NSE), and matrix metalloproteinase-9 (MMP-9), were consistently associated with worse functional outcomes, increased mortality, and higher risk of complications including hemorrhagic transformation and MBE.Multiple biomarkers demonstrate prognostic value in AIS patients undergoing MT. These findings may support risk stratification and individualized care, though further prospective studies are needed to integrate these biomarkers into the clinical practice.
Keywords: Ischemic Stroke; Thrombectomy; Biomarkers; Treatment Outcome